2000
DOI: 10.1243/0954406001522831
|View full text |Cite
|
Sign up to set email alerts
|

Non-destructive examination of adhesively bonded structures using dielectric techniques: Review and some results

Abstract: The use of high-frequency dielectric measurements is described for the non-destructive evaluation of adhesively bonded structures. Frequency domain measurements have been used to monitor the ingress of moisture into the joint structure. A good correlation has been observed between the data obtained from gravimetric and dielectric measurements. On prolonged exposure to water, changes occur to the surface oxide in the case of aluminium/aluminium joints to produce a surface hydroxide. The conversion process of ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 18 publications
0
14
1
Order By: Relevance
“…In previous publications, the use of dielectric measurements to monitor the water ingress into adhesively bonded structures and also the conversion of surface oxide to hydroxide have been reported [8]. An investigation by Li et al [9] of etched only, phosphoric and chromic acid anodized joints indicated that the changes in the dielectric profile with time reflected possible differences in the mechanism of ageing.…”
Section: Introductionmentioning
confidence: 99%
“…In previous publications, the use of dielectric measurements to monitor the water ingress into adhesively bonded structures and also the conversion of surface oxide to hydroxide have been reported [8]. An investigation by Li et al [9] of etched only, phosphoric and chromic acid anodized joints indicated that the changes in the dielectric profile with time reflected possible differences in the mechanism of ageing.…”
Section: Introductionmentioning
confidence: 99%
“…To measure thermal degradation, NDE techniques must be capable of detecting initial heat damage, which occurs on a molecular scale. 9,[12][13][14][15][16][17] These techniques essentially detect molecular changes in the polymer matrix subjected to thermal exposure. However, these NDE methods are based on chemical surface analysis, so they are still questionable for the prediction of bulk mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…High-frequency dielectric measurements have also been used for NDE of adhesive joints. [12][13][14] The influence of humidity on dielectric properties is well documented for thermoset resins and their composites. 19-23 E r and the loss factor increase with humidity.…”
Section: Introductionmentioning
confidence: 99%
“…It has applications in many areas such as nondestructive testing (NDT), radar and oil-pocket location. An NDT problem associated with the aircraft industry is that of testing adhesively bonded joints in airframe structures [1]. The bonds can become weakened by bird strikes, lightning, or thermal stress, eventually leading to water ingress, oxydation and bond failure.…”
Section: Introductionmentioning
confidence: 99%